2006
DOI: 10.1016/j.poly.2005.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Competitive formation of spiro and ansa derivatives in the reactions of tetrafluorobutane-1,4-diol with hexachlorocyclotriphosphazene: A comparison with butane-1,4-diol

Abstract: Beşli, Serap; Coles, Simon J.; Davies, David B.; Eaton, Robert J.; Kılıç, Adem; Shaw, Robert A. (2006) Competitive formation of spiro and ansa derivatives in the reactions of tetrafluorobutane-1,4-diol with hexachlorocyclotriphosphazene: a comparison with butane-1,4-diol. Polyhedron 25 (4): [963][964][965][966][967][968][969][970][971][972][973][974] This is an author-produced version of a paper published in Polyhedron . This version has been peer-reviewed, but does not include the final publisher proof corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…We have also shown that lithiated diols react quite differently with fluorophosphazenes when compared to silylated diols with the former forming preferentially the kinetically controlled ansa substituted products [9]. Comparison of reactions of disodium and dilithium salts of a diol with N 3 P 3 Cl 6 also shows interesting differences in the nature and yield of cyclized products [12]. In this context, we were interested in exploring the reactions of gem-diphenyltetrafluorophosphazene, [1,1-(C 6 H 5 ) 2 ]P 3 N 3 F 4 (1) with difunctional reagents, especially with dilithiated diols.…”
Section: Introductionmentioning
confidence: 78%
“…We have also shown that lithiated diols react quite differently with fluorophosphazenes when compared to silylated diols with the former forming preferentially the kinetically controlled ansa substituted products [9]. Comparison of reactions of disodium and dilithium salts of a diol with N 3 P 3 Cl 6 also shows interesting differences in the nature and yield of cyclized products [12]. In this context, we were interested in exploring the reactions of gem-diphenyltetrafluorophosphazene, [1,1-(C 6 H 5 ) 2 ]P 3 N 3 F 4 (1) with difunctional reagents, especially with dilithiated diols.…”
Section: Introductionmentioning
confidence: 78%
“…27,34 There are two different meso forms-one has a center of symmetry and the other has a plane of symmetry-which are formed with equal probability as mixture of diastereoisomers. In this case, two sets of closely spaced NMR signals of equal intensity should be expected for the mixture of diastereoisomers (which would indeed result in a doubling of the NMR signals for both the P(OR)Cl and PCl groups).…”
Section: P Nmr Studiesmentioning
confidence: 99%
“…39 Similar results were also obtained from the reaction of 1 with 1,4-butane-, 1,5-pentane and 1,6-hexane fluorinated diols. 20,27,30 Bridged compounds were obtained in better yields and assumed significant importance for reaction of 1 with diamines of increasing chain lengths and for the diols having the linking -(CH 2 ) n -group with n = 5, 6, 8, and 10, respectively. 28 We have previously reported that the reaction of hexachlorocyclotriphosphazene 1 with 2,2-dimethylpropane-1,3-diol 1 and bis(2-hydroxyethyl) ether 2 leads, in general, to the formation predominantly of spiro and ansa structures (Schemes 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
“…For products from the reaction of N 3 P 3 Cl 6 with bifunctional reagents, see: Beşli et al (2006). For N/O donor type bifunctional reagents used for the reaction of hexachlorocyclotriphosphazene giving spiro derivatives, see: Beşli et al (2007); Sournies et al (1997); Deutsch & Shaw (1990); Işıklan et al (2010); İlter et al (2004, 2007); Tercan et al (2004).…”
Section: Related Literaturementioning
confidence: 99%